(untitled) (Research, Society and Development, 2022)
The mental health of women in the puerperal period has become a challenge. Even though the physiological, anatomical, endocrinological, and also psychological changes are notorious, it is still neglected by the integral look at the newborn in this period, which can cause psychological harm to the same. The main objective of this work was to demonstrate the importance of the approach by the Nurse to the woman during the prenatal period on the prevention of mental health problems related to the puerperium. The research carried out has a qualitative character. For this, a Semi-structured script of an interview via video was applied to the 2020 Zoom 5.0 platform to collect data about the problem related to women’s mental health in the puerperium. With the present research, it was observed that the majority of postpartum women, in prenatal consultations, had mental health as a topic addressed. However, they still had feelings of insecurity, anxiety, stress, sleep deprivation, sadness, and sudden changes in mood related to this period. Therefore, the study emphasizes the importance of nurses creating a relationship of trust with women, welcoming them during this new period, so that they share fears and anxieties, helping nurses to conduct care in the face of the situation of mental health of the puerperal woman, reassuring her and minimizing further damage.